The influence of learning motivation, exposure to English, and learning strategies on English proficiency of Muslim students in Indonesia - Eva Fatimah; Nanang Nurcholis; Khoiriyatun Widyastuti; Anisya Maulidia; Luluk Nur Mufidah (Universitas Muhammadiyah Malang, 2025)
This study identifies the influence of various factors on students' English language skills. This study aims to investigate the extent to which Learning Motivation, English Exposure, and Learning Strategies, influence English Language Proficiency among Universitas Wahid Hasyim Pesantren Students at the Faculty of Economics and Business. This research would use quantitative research that has results that can be calculated to provide data. data analysis using (Sturctural Equation Modeling) SEM-PLS to determine the effect of Learning Motivation, English Exposure, and Learning Strategy on English Proficiency. The results showed that direct exposure to English, such as listening, speaking, and active use of the language, had thse most significant positive influence on English language proficiency. Learning motivation contributes positively, but the impact tends to be weak if it is not followed by real actions. Meanwhile, the learning strategies applied in this context show a negative influence, likely due to the incompatibility or ineffectiveness of the strategies used. These findings emphasize the importance of hands-on experience with the language.